2016
DOI: 10.1097/eja.0000000000000388
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of chemokine ligand 20 and chemokine receptor 6 in patients with sepsis

Abstract: There were early increased plasma concentrations of CCL20 and CCR6 in patients with sepsis. CCL20 and CCR6 correlate with severity of illness in ICU patients. Levels of CCR6 predicted the length of patients' admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…24,25 Several animal studies have confirmed that MIP-3 alpha is involved in the progression of severe inflammation, [26][27][28] and a recent study demonstrated that the MIP-3 alpha-driven cascade promoted the development of systemic inflammation in patients with severe sepsis. 29 They demonstrated plasma levels of MIP-3alpha in ICU patients with sepsis were elevated. Consistent with previous research, this study revealed that the concentration of MIP-3alpha in the death group was significantly higher than that in the survival group.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Several animal studies have confirmed that MIP-3 alpha is involved in the progression of severe inflammation, [26][27][28] and a recent study demonstrated that the MIP-3 alpha-driven cascade promoted the development of systemic inflammation in patients with severe sepsis. 29 They demonstrated plasma levels of MIP-3alpha in ICU patients with sepsis were elevated. Consistent with previous research, this study revealed that the concentration of MIP-3alpha in the death group was significantly higher than that in the survival group.…”
Section: Discussionmentioning
confidence: 99%
“…In sepsis patients, the population of B-PG#1 (CCR6 high CCR7 low HLA-DR low subset) was increased, while that of B-PG#2 (CCR6 low CCR7 mid HLA-DR high subset) was decreased. Since CCR6 is a crucial component in B cell immune responses and is associated with serious organ failure, 32 the elevated CCR6 in the B-PG#1 subset implies its role in sepsis-driven B cell activation. Furthermore, as the elevation of CCR7 expression is closely related to the differentiation of pre-B cells to the immature and mature stages, 33 the low CCR7 expression in B-PG#1 indicated a malfunction in B cell differentiation.…”
Section: ■ Discussionmentioning
confidence: 99%